2021
DOI: 10.1007/s11063-021-10602-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A Measurement Approach Using Smart-IoT Based Architecture for Detecting the COVID-19

Abstract: The corona virus has infected the entire world in the most severe ways. Many countries found the situation is very difficult to deal with and their health support infrastructure is not sufficient to manage the spread. People are locked in their homes and the whole world economy is in danger. That final vaccine has not yet reached the masses to deal with the epidemic. The corona virus, also known as COVID-19, can be spread by touching or coming close contact with an affected person, which is why the risk become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…If people need high precision and yet do not need a humanreadable method, the KNN algorithm is perfect. We can mainly evaluate forecasts based on distance metrics [38].…”
Section: K-nearest Neighbormentioning
confidence: 99%
“…If people need high precision and yet do not need a humanreadable method, the KNN algorithm is perfect. We can mainly evaluate forecasts based on distance metrics [38].…”
Section: K-nearest Neighbormentioning
confidence: 99%
“…The authors concluded that the IoT technology backed up by Fog-Cloud could overcome the limitations faced by the healthcare professional for the management of COVID-19 data. Poongodi et al [35] proposed a robust and smart healthcare system for enhancing COVID-19 management using IoT technology. The proposed architecture depicted enhanced accuracy compared to the state-of-the-art computing techniques for statistical parameters.…”
Section: Related Workmentioning
confidence: 99%
“…The RNN is prepared for this single " end-to-end " organization [15][16][17][18][19][20][21][22][23][24]. The model is driven by late succession age achievements in machine interpretation, with the distinction that we give a picture managed by a convolutionary net instead of starting with a sentence [25][26][27][28][29][30][31][32][33][34][35][36][37][38], who uses a neural net to predict the next word, given the picture and past words, but a feedforward one. A continuous work by [39] uses the repetitive NN for the equivalent assignment of expectations.…”
Section: Related Workmentioning
confidence: 99%